Mpox Disease Transmission, Clinical Presentation and Prevention : Article Review - Madfoon, Zainab Mohammed; AbdulRedha , Haider Abass; Zghair, Liqaa Salim (Medical Science Journal for Advance Research, 2025)
"Mpox one of zoonotic disease"(WHO), in 1958 are first discovered monkeys , the viruse that responsible of these disease belong to the genus Orthopoxvirus , a member of the Poxviridae family. It gained significant attention in the 1970s when first cases for human were recorded, particularly in Central, West Africa.The spread of recent outside these endemic areas has raised global concerns. This article discusses monkeypox, its clinical features, and prevention strategies. Direct contact with infected animals causes transmission to humans. transmitted of virus from person to person by respiratory droplets, skin attached , and sexually. The fever, swollen lymph nodes consider most common symptoms in monkeypox patients also rash that progresses through many stages before recovery. The immunocompromised individuals experience complications like secondary bacterial infection and severe systemic problems. Although there is no specific cure, antiviral like tecovirimat and supportive care have shown promising results. Vaccination remains a critical preventive measure, especially for the most vulnerable groups. Understanding the epidemiology, pathogenesis, and effective control strategies is essential to mitigate the global impact of viral infection.